El phishing como medio de disposición patrimonial fraudulenta - Campoverde Salas, Valeria Alejandra (2023)
Nowadays the advances in information and communication technology growth with the time giving many facilities in different aspects of life, above all how the people develop into society. Furthermore, it presents some consequences or disadvantage, as for example: The characteristic of free access to any person: It does not have a limit of age. Sometimes these users give a number of personal information in any platforms that exists: for instant the social media or shopping in line. Even, nobody is out of the big influence of these advances because these have done an emergent of a serial behaviour or ilicit forms which are called: “cybercrime”. So. There are various forms in which cityzenships of any country can be victims of fraud and deceit through the virtual platforms, hence, it is observed the necesity to give the kind of crine which is having the most attendance in the actuality, which is the cybercrime “Phishing”.It will inform the form of development, the finality that have the infractors to do or the motive they have to commit the criminal act. During the development of the research work I will develop and approach topics that help to identify the implications and damage caused by this crime, showing how are vulnerable the economic and patrimonial rights of people; so that, phishing is considered as a product of technology which advances with a major intensity. For achieving a complete researching of this thematic, it is established a respective conceptualization about some terms which are related with the topic to understand in a best way; furthermore, it is mentioned a history review about the technology of information and communication (TIC) with its characteristics, advantage, and disadvantage. It is adressed the cybercrime define the human being that intervene into it and the social repercussion which is produced in the actuality; Next it is given, what does it mean nowadays in the social media with its respective characteristics, advantage and disadvantage; finally it is adressed in a general way the origin and definition of cybercrime of phishing, which are the types that exists, the phases which to get the objective of the cyber delinquents, the big impact that this crime has into society and some recommendations that should follow to do not be victims of it or avoid this class of infractors. It is included our constitutional criminal law to identify the economic and patrimonial properties protected. In addition. It is mentioned the normative international resources given by law, which have a high investigation. It is contributed an agreement of cybercrime 5 celebrated in Budapest that is a source and guide for the legislations of the different Europe countriesthat they have typified the crime of phishing in an autonomun and independent way. I conclude this investigation with the approach of a legal porposing adapted to the reality of the society, principally it is based in the fundaments or arguments which are extracted of a legal study that is developed. Therefore, it is mentioned the legality beginning, which is fundamental for sanction a person and make a literal interpretation ofthe norm. With this. It is verified the necesity to integrate the cybercrime of physhing to the Integral Organic Legal Code in order to it does not vulnerable the patrimonial and property of people.